PERTUMBUHAN DAN TINGKAT KELANGSUNGAN HIDUP SPAT KERANG MUTIARA (Pinctada maxima) DENGAN KOMBINASI FITOPLANKTON Chaetoceros amami DAN Nitzschia sp. - Auliyah, Annisah Nur; Mukhlis, Alis; Asri, Yuliana (Journal of Fish Nutrition, 2023)
This study aims to evaluate the effect of the combination of Chaetoceros amami and Nitzschia sp. phytoplankton as natural food for the growth and survival of pearl oysters (Pinctada maxima). The experimental method was used with five different treatments consisting of treatment A = C. amami 100%; B = C. amami 75% + Nitzschia sp. 25%; C = C. amami 50 % + Nitzschia sp. 50%; D = Nitzschia sp 75% + C. amami 25%; E = Nitzschia sp 100%. Each treatment was repeated 3 times and the experimental units were randomly assigned using a Completely Randomized Design (CRD). This research aims to assess the optimal natural feed for pearl oyster spat. The results of this study showed that feeding in combination had a significant effect (P<0.05) on the growth value of pearl mussels (P. maxima), the highest value of absolute growth of pearl mussels (P. maxima) which was maintained for 21 days was obtained, namely in treatment B (C. Amami 75% + Nitzschia sp 25%) with a mean ± SD size of 7.5 ± 0.2 mm and the highest survival rate results in treatment B (C. amami 75% + Nitzschia sp 25%) namely 89%. The results of this research are expected to provide valuable insights into the suitable natural feed to support the growth and survival of pearl oyster spat.